Efektivitas Metode Pembelajaran Baca Tulis Al-Qur’an (BTQ) Terhadap Kemampuan Membaca Al-Qur’an santri Cilik TPQ Darunnajah Jakarta - Sofwan Manaf; rokimin; Bayu Arif Mahendra; Romidi (Universitas Darunnajah, Jakarta, Indonesia, 2023)
Abstract This research aims to determine the effectiveness of the Al-Qur'an Reading and Writing Learning Method (BTQ) on the Al-Qur'an Reading Ability of the young students of TPQ Darunnajah Jakarta, the method used, as well as supporting and inhibiting factors for the Al-Qur'an Reading and Writing program . The methodology used is descriptive qualitative, specifically involving the description of observed events. The goal is to extract information that will form the basis of conceptual design. Information is obtained from official sources such as reference books, magazines, documents, and laws. Data collection methods were obtained by observation, documentation and interviews with TPQ Darunnajah. This research determines that the effectiveness of reading and writing the Al-Qur'an has a positive impact on improving the Al-Qur'an reading skills of TPQ Darunnajah students so that it is classified as effective. The effectiveness of the Al-Qur'an Reading and Writing curriculum at TPQ Darunnajah can be seen from its ability to significantly increase students' fluency in reading the Al-Qur'an. The technique used is the Ummi method. Consistency in program implementation is the main supporting component, even though there are many obstacles. An obstacle that hinders progress is the limited time allocated for studying at educational institutions.